Updated annotation and meta-analysis of Brugia malayi transcriptomics data reveals consistent transcriptional profiles across time and space with some study-specific differences in adult female worm transcriptional profiles. - Christopher I Holt; Julie C Dunning Hotopp (Public Library of Science (PLoS), 2024)
Genomics, transcriptomics, and proteomics have significantly advanced our understanding of obligately host-associated microbes, where interrogation of the biology is often limited by the complexity of the biological system and limited tools. This includes the causative agents of many neglected tropical diseases, including filarial nematodes. Therefore, numerous transcriptomics studies have been undertaken on filarial nematodes. Most of these transcriptomics studies focus on Brugia malayi, which causes lymphatic filariasis and is a laboratory model for human filarial disease. Here, we undertook a meta-analysis of the publicly available B. malayi transcriptomics data enabling the direct cross comparison of samples from almost a dozen studies. This reanalysis highlights the consistency of transcriptomics results across many different studies and experimental designs from across the globe for over a decade of research, across many different generations of a sequencing technology, library preparation protocols, and differential expression tools. Males and microfilariae across samples had similar expression profiles. However, female samples were clustered into two differential expression patterns that were significantly different from one another. Largely, we confirm previous results for all studies reanalyzed including tissue-specific gene expression and anti-Wolbachia doxycycline treatment of microfilaria. However, we did not detect previously reported differential expression upon in vitro or in vivo treatment with ivermectin, albendazole, and DEC, instead identifying a consistent lack of transcriptomic change upon exposure to these anthelminthic drugs. Updated annotation has been provided that denotes poorly supported genes including those overlapping rRNAs.